The Picaresque in the 18th century English Novel - Shahmuradyan, Anahit (Armenian Folia Anglistika, 2008)
The Picaresque novel was one of the first steps of the establishment of the Spanish realist novel in early Renaissance period. The Picaresque theme found its direct reflection in the 18th century English novel. Both Daniel Defoe in his Moll Flanders, Captain Singleton and other works, Jonathan Swift in his Gulliver’s Travels and Henry Fielding in his The history of Tom John, a Foundling wish to reveal the true picture of the values and morals of the time, the real strives and face of man, the social motives which often create inextricable situations for people and promote picaresque actions making them become a thief and picaroon.